2011
DOI: 10.1097/prs.0b013e318230c55d
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Are Required in the Proliferation and Remodeling Phases of Microdeformational Wound Therapy

Abstract: Mast cells are critical in the robust granulation tissue response seen in microdeformational wound therapy and in the modulation of the remodeling phase of wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…They form intimate connections with keratinocytes and fibroblasts through gap junctions. 7 It has been shown that mast cells are involved in all three phases of wound healing 8,9 -the inflammatory, proliferative, and remodeling phases 10 -however, the exact mechanism of mast cell involvement has not been fully revealed. 11 The release of the granule contents (exocytosis) is dependent on the types of receptors on the mature mast cell and on the activating agents in the respective tissue.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…They form intimate connections with keratinocytes and fibroblasts through gap junctions. 7 It has been shown that mast cells are involved in all three phases of wound healing 8,9 -the inflammatory, proliferative, and remodeling phases 10 -however, the exact mechanism of mast cell involvement has not been fully revealed. 11 The release of the granule contents (exocytosis) is dependent on the types of receptors on the mature mast cell and on the activating agents in the respective tissue.…”
mentioning
confidence: 99%
“…12 Mast cells can degranulate in response to various biochemical and immunogenic agents (e.g., immunoglobulin E, complement proteins, and growth factors 13,14 ) and in response to physical stimuli, which include sunlight (sunlight is really electromagnetic radiation), radiation, trauma, and mechanical stretch. 7 Of note, mast cells possess transient receptor potential vanilloid channels on their membranes that are activated by mechanical stimulation and lead to calcium influx through specific ion channels, which eventually causes the mast cell to degranulate. 15 Microdeformational wound therapy, also referred to as negative-pressure wound therapy, uses a porous polyurethane foam under vacuum to induce microdeformations on the wound edge 16,17 and is used clinically for the treatment of complex wounds.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Wound healing is a complex process of lysis and reconstitution controlled by a series of cell signaling proteins and involved tissue regeneration and angiogenesis (Hiromatsu and Toda 2003;Nienartowicz et al 2006). Mast cells have been shown to play a significant role in the early inflammatory stage of wound healing and also influence proliferation and tissue remodeling in skin; according to some authors in wound healing, mast cells are able to modulate only the inflammatory but not the proliferative response in healing and reconstituting damaged tissue (Egozi et al 2003), while other reports showed that mast cells are involved in tissue remodeling in the late phase of wound healing (Iba et al 2004), thus expanding the debate about the role of mast cells in tissue remodeling (Kennelly et al 2011;Younan et al 2011;Garner and Ehrlich 2011). The role of inflammatory cells, including those factors commonly associated with allergy such as basophils and mast cells, is involving many other unexpected fields, such as cancer (Heneberg 2011) and obesity (Zhang and Shi 2012).…”
mentioning
confidence: 99%